Synthesis and biological evaluation of resveratrol derivatives with anti‐breast cancer activity. Issue 7 (28th April 2020) - Yang, Mei‐Fang; Yao, Xu; Chen, Li‐Mei; Gu, Jin‐Ying; Yang, Ze‐Hua; Chen, Hong‐Fei; Zheng, Xing; Zheng, Zi‐Tong
Abstract: Resveratrol is a natural phytoestrogen produced by plants to protect themselves from injury, UV irradiation, and fungal attack. The main active structure is E ‐resveratrol, which has many pharmacological activities. As the structure of resveratrol is similar to the natural estrogen 17β‐estradiol and the synthetic estrogen E ‐diethylstilbestrol, resveratrol is used in reducing the incidence of breast cancer. However, the therapeutic application of resveratrol is limited due to its low bioavailability. To improve its bioavailability and pharmacological activity, some resveratrol derivatives have been designed and synthesized by substitutions of methoxy, hydroxyl, and other functional groups or heterocyclic esterification either on the "A" or "B" ring, and double bonds were replaced by imine bonds and isometric heterocycles such as naphthyl and imidazole, or synthetic resveratrol oligomers. The structures, synthetic routes, and evaluation of the biological activities of these compounds are discussed. These are aimed at providing some references for the study of resveratrol derivatives in anti‐breast cancer treatment. Abstract : Resveratrol is used in reducing the incidence of breast cancer. To improve its bioavailability and pharmacological activity, some resveratrol derivatives have been designed and synthesized by substituting functional groups, heterocyclic esterification on the "A" or "B" ring, and replacement of double bonds. The structures, synthetic routes, and evaluation of the biological activities of these compounds are discussed.